The Agility Factor Building Adaptable Organizations for Superior Performance - Worley, Christopher G. (Wiley, 2014)
A research-based approach to achieving long-term profitability in business What does it take to guarantee success and profitability over time? Authors Christopher G. Worley, a senior research scientist, Thomas D. Williams, an executive advisor, and Edward E. Lawler III, one of the country's leading management experts, set out to find the answer. In The Agility Factor: Building Adaptable Organizations for Superior Performance the authors reveal the factors that drive long-term profitability based on the practices of successful companies that have consistently outperformed their peers. Of the 234 large companies across 18 industries that were studied, there were few companies that delivered sustained performance across the board. The authors found that across industries, the most successful companies were not the "usual suspects" found in the media, but companies who possessed a quiet agility that allowed them to quickly perceive and respond to changes so that they could continue to grow. Agility gives organizations the ability to adapt to fluctuations in the environment, test possible responses, and implement changes quickly. This book offers specific, research-based case studies to help organizational leaders use agility to achieve sustained profitability and performance while also becoming more adaptable to a changing marketplace. For executives, leaders, consultants, board members and all those responsible for the long-term health of organizations, this insightful guide outlines: The components of agility for business organizations How to successfully build agility within an organization How agility has its foundation in good management practices How to use agility to gain a competitive advantage in the marketplace
Description based on publisher supplied metadata and other sources
Keywords: Organizational change -- Management; Organizational effectiveness; Organisation; Management; Effizienz; Organisationswandel